Role of PACAP in Migraine Headaches - J Gordon Millichap; John J Millichap (Pediatric Neurology Briefs Publishers, 2014)
Investigators at Danish Headache Centre, University of Copenhagen, Glostrup, Denmark, studied the incidence of migraine during and after intravenous infusion of pituitary adenylate cyclase-activating polypeptide-38 (PACAP38) and vasoactive intestinal polypeptide (VIP) in 22 female migraine patients without aura (mean age 24 years [range 19-36]).